SISTEM INFORMASI GEOGRAFIS PROYEK BETONISASI JALAN DI KABUPATEN DEMAK BERBASIS WEB (Information Technology and Telematics, 2013)
Demak regency is one of the districts in the region north coast line, the density of the traffic intensity in Demak regency requires special attention to the access road used by the public. Each year, Demak regency has always held a development of the road infrastructure. With concrete construction, the road infrastructure to be more durable and not easily damaged. Issues examined in this study is the lack of information to the public about the development of road infrastructure in Demak regency. The purpose of this study is to provide information regarding the location of road concretisation has been done in the year 2009 - 2011 with easy and fast. Geographic Information Systems (GIS) was developed with the PHP programming language, MySQL database and ArcView. GIS can provide location information along with the name of the road and concretisation contractor in Demak Regency and the information can be easily accessed via internet. GIS is expected to help the people to know the development of road infrastructure development up to date.Keywords: Geographic Information Systems, Road Infrastructure, MySQL